(untitled) (Papeles, 2023)
This is a work product of the line of research that since 2004 has been develops as a research team, where we have studied the constitution of the field professional in various historical moments of Social Work. Within the framework of the current research project "Collective Memories: places of memory and commemorations in territorial spaces of the city of Córdoba”, we have addressed from oral history the reconstruction of the collective memory of various territories of the city ​​of Córdoba, this presentation focuses on the Alberdi neighborhood, the cradle of various historical milestones of our contemporary history: Reform of 18, Cordobazo, but there are another story, the story of its first settlers, the aboriginal people. at this writing we intend to analyze these “other voices”.